Benefit assessment of extended dosing in cancer patients after their withdrawal from clinical trials - Yang, Feng; Huang, Zhe; Heng, Jianfu; Li, Kunyan (Frontiers in Pharmacology, 2023)
Background: Clinical trials have been widely recognized as an effective treatment approach by physicians and cancer patients alike. Physicians' evaluations suggest that many patients are likely to continue experiencing benefits from extended dosing of investigational new drugs even after withdrawing from clinical trials.Objective: Given the uncertainty surrounding the efficacy and safety of investigational new drugs, it is essential to continually assess the benefits of extended dosing for patients.The trial group for this study comprised patients who requested extended dosing after withdrawing from clinical trials at Hunan Cancer Hospital between 2016 and 2020. The control group consisted of patients who received conventional treatment and were enrolled in a 1:1 ratio. Follow-up assessments were conducted every 3 months for both groups, and included monitoring of patients' health status, survival time, disease control or remission, treatment modalities received, and medical costs.Results: A total of twenty-three patient pairs were successfully matched for this study.The Ethics Committee approved extended dosing for all patients in the trial group, with an average gap period of 16.48 days between their withdrawal from clinical trials and continuous access to the investigational drugs. The median overall survival for patients after withdrawal from clinical trials was 17.3 months in the extended dosing group and 12.9 months in the control group, with no significant difference observed between the two groups (p > 0.250). The median total cost of treatment after the previous clinical trial was 38,006.76 RMB, of which the median cost of therapeutic drugs for conventional treatment was 15,720 RMB, while extended dosing was provided free of charge.Extended dosing can indeed provide benefits, including survival benefits and economic benefits, to cancer patients after their withdrawal from clinical trials and will clinically present an additional treatment option for patients.